Liderazgo directivo y su influencia en el desempeño profesional de la secretaria auxiliar de la Unidad Educativa Quevedo, del Cantón Quevedo año 2016. - Boza Romero, Lisseth Gabriela (2016)
Before the new requirements on the subject of executive leadership, demanding institutions is considered necessary to have two very clear aspects in education, which is the professional performance and other communication and ethical integration of the secretary. It is also important to note that management leadership and job performance in educational institutions has important determinants of leadership style that employs and applies each leader. In an educational institution, should not aim and ideal achieve quality and efficiency in the exercise of Leadership promoting this through people within the educational community, which is why we must provide better service to teachers and thus provide service teachers and students of the Education Unit Quevedo. This project expects to achieve clear objectives within the research as this will help to determine what factors were used to fulfill are, you can also view all of this by the statistical graphs that give us exactly the percentage of the results if it is achieved or not achieved and accordingly proposed alternatives. In addition, an alternative proposal which will serve to resolve the issues raised and propose new objectives and will contribute to this alternative proposal was raised which will pose to solve the problem in research, which is needed the participation of the authorities of the Education Unit Quevedo